2022
DOI: 10.3390/nano12203656
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healable Lithium-Ion Batteries: A Review

Abstract: The inner constituents of lithium-ion batteries (LIBs) are easy to deform during charging and discharging processes, and the accumulation of these deformations would result in physical fractures, poor safety performances, and short lifespan of LIBs. Recent studies indicate that the introduction of self-healing (SH) materials into electrodes or electrolytes can bring about great enhancements in their mechanical strength, thus optimizing the cycle stability of the batteries. Due to the self-healing property of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…For example, at low temperatures, lithium ion batteries (LIBs) often suffer from reduced capacity and a sharply declined lifetime due to decreased Li + diffusion within both the electrodes and electrolyte [105,106]. At high temperatures, LIBs also show a drop in capacity, increased internal resistance, degradation of the electrodes and electrolyte, and even safety risks such as thermal runaway (TR), which triggers a chain reaction that can result in catching fire or an explosion [107,108]. By undergoing reversible melting and solidification, hydrated salts can absorb excessive heat in a timely manner and release the latent heat when the temperature of the electronic device drops below the freezing point of the PCM, thus offering a facile method for the passive thermal management of electronic devices [10,29].…”
Section: Thermal Management Of Electronic Devicesmentioning
confidence: 99%
“…For example, at low temperatures, lithium ion batteries (LIBs) often suffer from reduced capacity and a sharply declined lifetime due to decreased Li + diffusion within both the electrodes and electrolyte [105,106]. At high temperatures, LIBs also show a drop in capacity, increased internal resistance, degradation of the electrodes and electrolyte, and even safety risks such as thermal runaway (TR), which triggers a chain reaction that can result in catching fire or an explosion [107,108]. By undergoing reversible melting and solidification, hydrated salts can absorb excessive heat in a timely manner and release the latent heat when the temperature of the electronic device drops below the freezing point of the PCM, thus offering a facile method for the passive thermal management of electronic devices [10,29].…”
Section: Thermal Management Of Electronic Devicesmentioning
confidence: 99%
“…[132] The primary challenge associated with Si anodes is the structural degradation and instability of the SEI owing to the substantial volume change (≈300%) during lithiation (Figure 2B). [52,53,56] This can lead to electrode delamination from the current collector. [133] Consequently, side reactions with the electrolyte occur, causing severe structural pulverization and rapid capacity fading of the electrode.…”
Section: Anode Degradationmentioning
confidence: 99%
“…[148,210] Self-healing mechanisms includes autonomous and nonautonomous, and thus their behaviors enable to be classified into the physical, chemical, and physical-chemical synthetic approaches. [53,131] Therein, self-healing materials applied in LIBs presently have primarily used chemical approaches to achieve self-healing capability. The chemical approaches are either reversible chemical bonds or supramolecular interactions.…”
Section: Self-healing Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 Noteworthily, the dynamic covalent bonds can not only provide a robust cross-linked network but also endow binders with self-healing properties, which contributes to the stable electrode structure. 35,36 It is widely known that introducing dynamic boronic esters is an efficient way to form self-healing polymers due to the reversible exchange of B–O bonds. A previous study has confirmed that the reversible exchange of B–O bonds can be encouraged by the extra hydroxyl group in the pyrogallol structure, in which the extra hydroxyl group functions as a proximal base.…”
Section: Introductionmentioning
confidence: 99%